Patterns and environmental drivers of diversity and community composition of macrofauna in the Kveithola Trough (NW Barents Sea) - CARIDI, FRANCESCA; Sabbatini Anna; Morigi Caterina; Dell'Anno Antonio; Negri Alessandra; Lucchi Renata Giulia (Journal of Sea Research, 2019)
The Kveithola Trough located in the NW Barents Sea is a peculiar system characterized by distinct geomorphological and environmental features which are expected to exert an important role on the distribution of benthic assemblages. In the present study we investigated for the first time the distribution of macrofaunal abundance, biomass and diversity along the Kveithola Trough. Our analysis reveals major differences of the macrofaunal assemblages along the Kveithola Trough related not only to the different morpho-depositional features but also to differences in trophic conditions. The inner part of the Kveithola Trough was characterized by the presence of opportunistic species such as Levinsenia gracilis and Maldane sarsi among polychaetas, Mendicula cf. pygmea and Yoldiella sp. among bivalves, which are known to inhabit oxygen-depleted environments and organic-enriched sediments. Results reported in this study suggest that the peculiar environmental conditions of the Kveithola Trough along with the occurrence of methane seepage in the neighbouring Storfjorden Trough in association to the Knølegga fault may exert a major selective effect on macrofaunal organisms.